A task scheduling model integrating micro-breaks for optimisation of job-cycle time in human-robot collaborative assembly cells. Issue 15 (3rd August 2022) - Zhang, Ming; Li, Chunquan; Shang, Yuling; Huang, Hongyan; Zhu, Wangchun; Liu, Yujia
Abstract : Human-Robot Collaboration, whereby human worker and robot perform tasks jointly, is becoming the new frontier in industry production. Unlike robots, continuous work leads to an accumulation of human fatigue, which is the main cause of decreased efficiency and deterioration of health. Characteristic differences between human and robot bring challenges to collaboration task scheduling. In this paper, we studied the task scheduling of a human-robot collaboration assembly cell to achieve a trade-off between job cycle and human fatigue. A task scheduling model integrated with micro-breaks inside job cycles was proposed to avoid human fatigue accumulation by taking advantage of the human-robot collaboration characteristics. Furthermore, the optimisation of task scheduling by taking the job cycle as the objective function and maximum human fatigue as a constraint was solved. The developed method is studied on a cable assembly inspired by an industry case. The results of the case study are presented to indicate the validity and practicability of the proposed model. It suggests that compared with the model of placing rest breaks between job cycles, the proposed model outperforms in job-cycle performance in most cases. Finally, there are some insights on the HRCAC which are obtained from the results of the case study.